Strategi Dinas Ketenagakerjaan Dalam Menanggulangi Pengangguran di Kabupaten Bandung - Jelita Maelani; Maya R Atmawinata (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The fluctuating unemployment trend in Bandung Regency represents a key issue that requires targeted intervention from the local Manpower Office. This research aims to explore the regional government’s strategic efforts to reduce unemployment, evaluate the impact of workforce training programs, and examine the role of inter-sectoral cooperation. Adopting a descriptive qualitative method, data were obtained through interviews, observation, and documentation. The findings highlight various strategies such as industry-aligned skills training, partnerships with the private sector, and the use of digital platforms to facilitate job placement. In times of economic downturn, the office implements labor-intensive work schemes and entrepreneurship training as responsive measures. Main challenges include mismatches in skills, limited access to employment information, and broader economic influences. While the strategies have shown positive outcomes in expanding job opportunities, further improvements are needed in institutional coordination and long-term program sustainability. The study underscores that collaborative and adaptive strategies are vital in reducing unemployment and boosting the competitiveness of the regional workforce.